3D assessment of surface influence on crack initiation in sharp notches under a mixed mode of loading. (April 2021) - Klusák, Jan; Kopp, Dalibor
Highlights: Crack initiation in specimens with a notch occurs mostly in centre of the specimens. In some cases crack initiates at surface (in a vertex point) of a notched specimen. Direction of external loading influences the crack initiation place significantly. 2D calculations can assess crack initiation reliably in central layer of the samples. To assess crack initiation in surface layer, 3D calculations are necessary. Abstract: Sharp notches occur in constructions and lead to stress concentrations. Thus they are dangerous points of constructions and must be properly evaluated. In the present study the effect of a free surface on crack initiation conditions is observed and evaluated by means of a 3D model of a specimen with a sharp notch and by means of the finite fracture mechanics of general singular stress concentrators (GSSCs). The effect of a free surface on crack propagation and the crack front shape is described in many publications (Hutař et al., 2010; He et al., 2016; Oplt et al., 2019). Concerning GSSCs (sharp notches, bi-material notches, sharp material inclusions, etc.) crack initiation conditions can also be influenced by the presence of the free surface. In our study we suppose the case of a sharp notch in a homogeneous material with a straight notch front perpendicular to the free surface. In this case a crack can be initiated either from the central region of the notch front or at the vertex point (the point where the notch front intersects the free surface). In order to assess the crack initiation conditions in the 3D model, the critical quantity criterion is employed (Klusák et al., 2019). This criterion can be easily used with the knowledge of basic material parameters and with the use of results of finite element calculations of the assessed notch. It is shown that the place of crack initiation depends on the direction of external loading and thus on a mixity of normal and shear modes of loading. A comparison of results of 2D and 3D models is discussed.